Revisiting the Examination of Sharp/Dull Discrimination as Clinical Measure of Spinothalamic Tract Integrity - Heutehaus, Laura; Schuld, Christian; Solinas, Daniela; Hensel, Cornelia; Kämmerer, Till; Weidner, Norbert; Rupp, Rüdiger; Franz, Steffen (Frontiers in Neurology, 2021)
Objective: Revisiting the sharp/dull discrimination as clinical measure of spinothalamic tract function considering the International Standards for Neurological Classification of Spinal Cord Injury (ISNCSCI). Three clinically relevant factors were evaluated as to their impact on reliability: (1) the localization of dermatomes in relation to the sensory level, (2) the examination tool, and (3) the threshold of correct answers for grading of a preserved sharp/dull discrimination. Design: Prospective monocentric psychometric study. Setting: Spinal Cord Injury Center, Heidelberg University Hospital, Germany. Participants: Convenient sample of 21 individuals with subacute spinal cord injury (age: 31–82 years) and 20 individuals without spinal cord injury (age: 24–63 years). Assessment: All participants underwent three assessments for sharp/dull discrimination, applying five commonly used examination tools in seven dermatomes, performed by three trained examiners under conditions in accordance with ISNCSCI. Main Outcome Measures: Assessment of interrater reliability by determining both the Fleiss kappa (κ) coefficient and the percentage agreement between raters. Data were dichotomized regarding the ISNCSCI threshold. Results: Interrater reliability in individuals with SCI was overall substantial (κ = 0.68; CI 0.679–0.681) and moderate (κ = 0.54; CI 0.539–0.543) in dermatomes below the sensory level. All applied tools led to at least moderate reliability below the sensory level (lowest κ = 0.44; CI 0.432–0.440), with the officially endorsed safety pin achieving the highest (substantial) reliability (κ = 0.64; CI 0.638–0.646). Percentage agreement differed between non-SCI (97.3%) and formally intact above level dermatomes in SCI (89.2%). Conclusions: Sharp/dull discrimination as a common clinical examination technique for spinothalamic tract function is a reliable assessment. Independent from the used examination tools, reliability was substantial, with the medium-sized safety pin delivering the most favorable results. Notwithstanding this, all other tools could be considered if a safety pin is not available. Regarding interrater reliability and guessing probability, a threshold of 80% correct responses for preserved sharp/dull discrimination appears to be most suitable, which is in line with current clinical approaches and ISNCSCI. The causal attribution of the identified differences in sharp/dull discrimination between clinically intact dermatomes of individuals with SCI and unaffected dermatomes of individuals without SCI requires future work. Clinical Trial Registration Number (German Clinical Trials Register): DRKS00015334 (https://www.drks.de).